Surgical management of recurrent pyogenic cholangitis: 10 years of experience in a tertiary referral centre in Hong Kong - Co, Michael (BlackWell Publishing Ltd, 2014)
BACKGROUND: Recurrent pyogenic cholangitis (RPC) is common in Asia. Its management differs from centre to centre. METHODS: A retrospective review of 80 patients undergoing surgery for RPC was performed. Immediate and longterm outcomes were analysed. RESULTS: All patients underwent hepaticocutaneousjejunostomy (HCJ) for biliary drainage and stone removal. Additional hepatectomy was performed in 38 patients with intrahepatic ductal stricture or liver segmental atrophy. Twenty-three patients had residual stones and 25 had recurrent stones. All patients with residual stones underwent repeated choledochoscopy (median: four sessions) for stone removal and obtained confirmation of ductal clearance. Four patients developed cholangiocarcinoma, of which two died. The complication rate was 17.5%. Most of the complications were wound infections. No mortality related to surgery occurred. Multivariate analysis found that gender, disease extent (unilobar versus bilobar) and surgery type (HCJ alone versus HCJ with hepatectomy) were not associated with increased risk for residual or recurrent stones. A raised preoperative bilirubin level was the only risk factor identified as associated with an increased risk for recurrent stones (P < 0.001); it was not associated with an increased risk for residual stones. CONCLUSIONS: Recurrent pyogenic cholangitis is a distinct disease, the management of which requires a high level of surgical expertise. Hepaticojejunostomy is recommended as the primary drainage procedure, but hepatectomy should be reserved for complicated RPC.